2019
DOI: 10.1002/hed.25614
|View full text |Cite
|
Sign up to set email alerts
|

Importance of tumor budding grade as independent prognostic factor for early tongue squamous cell carcinoma

Abstract: Background Factors involved in neck lymph node metastasis (NLM) and prognosis of early tongue squamous cell carcinoma (SCC) remain unknown. Methods We analyzed disease‐specific survival (DSS) and NLM including tumor budding grade (TBG) among 64 patients with cT1/2N0 tongue SCC. Results Univariate analysis of DSS of primary lesions uncovered significant differences in new cT, pT, new pT, pDiameter, venous infiltration, and TBG. Multivariate analysis selected only TBG3 as a predictor of NLM (odds ratio, 9.55; 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 22 publications
1
27
0
2
Order By: Relevance
“…the correlation of NLM with TBG, but they were limited to high TBG cases (13,14). In our previous study (15), we found that TBG is the most important prognostic factor for the early T-stage tongue SCC. High TBG indicates a high risk for NLM, and is superior to DOI at predicting NLM.…”
Section: Podoplanin Is An Efficient Predictor Of Neck Lymph Node Metamentioning
confidence: 79%
See 1 more Smart Citation
“…the correlation of NLM with TBG, but they were limited to high TBG cases (13,14). In our previous study (15), we found that TBG is the most important prognostic factor for the early T-stage tongue SCC. High TBG indicates a high risk for NLM, and is superior to DOI at predicting NLM.…”
Section: Podoplanin Is An Efficient Predictor Of Neck Lymph Node Metamentioning
confidence: 79%
“…Cytokeratin AE1/3-staining was useful for a less experienced pathologist (HM), as previously reported (23). The cases were divided into two groups: high TBG (TBG3) and low TBG (TBG1/2) based on previous studies (14,15).…”
Section: Methodsmentioning
confidence: 98%
“…In OTSCC, however, there is a gap between molecular research that has already documented the importance of tumor stroma and pathology practice which has so far not included the evaluation of stromal characteristics. Currently, histopathological grading according to the WHO criteria which are based on tumor differentiation is often routinely reported in daily pathology practice, although many studies have shown that this grading has a low prognostic value for early-stage OTSCC [7,[21][22][23][24]. In addition, differences between tumors of the same type are usually assessed by evaluating tumor-related features (e.g., pattern of invasion and depth of invasion).…”
Section: Discussionmentioning
confidence: 99%
“…The carcinoma cell invasion budding, as detected in SiHa invasion to myoma, have independently been connected in clinical studies with deeper invasion depth, venous invasion, lymph node metastasis and poor prognosis in head-and-neck squamous cell carcinoma (HNSCC) and colorectal cancer [31][32][33][34][35][36][37][38][39][40]. Also, both in Fig.…”
Section: Discussionmentioning
confidence: 90%